Empowering Women Farmers by Building Resilience to Heat Stress - Macwan, N.; Kori, Pooja; Verma, Benu; Puskur, Ranjitha (CGIAR GENDER Impact Platform, 2024)
As global temperatures rise, heat stress has become a major concern, particularly for rural communities engaged in agriculture. Rural women, who play a crucial role in agriculture, experience the disproportionate effects of heat stress due to their physiological differences, cultural norms, and socioeconomic challenges. In Ganjam district, Odisha, India, women farmers face significant difficulties from heat stress, which impacts their health, productivity and overall well-being. To address these challenges, the CGIAR GENDER Impact Platform, led by the International Rice Research Institute (IRRI) in collaboration with Awaas Sewa Pvt. Ltd (ASPL), organized a series of training workshops aimed at enabling women farmers to better understand and manage heat stress and also build resilience to heat and other climate-related challenges. The three part training workshops, held between August and October 2024, focused on women farmers from Pratappur and Atraipalli villages of Ganjam district. The first workshop raised awareness about the impacts of heat stress on both their agricultural and domestic activities. The second workshop brought in the Community-Based Vulnerability Assessment Tool (CBVAT) along with other tools to help farmers assess and understand climate-related vulnerabilities specific to their communities. The final workshop provided practical heat stress management strategies and solutions, and also aimed at empowering women with knowledge of locally available resources and coping mechanisms. The trainings helped build capacity, developed community-driven solutions, and ensured that women farmers are better equipped to tackle the growing challenges posed by heat stress. The workshops integrated expert guidance with participants' lived experiences, enhancing the resilience of rural women farmers.